Investigation and design of ion-implanted MOSFET based on (18 nm) channel length - Firas Natheer Abdul-kadir; Khalid khaleel Mohammad; Yasir Hashim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The aim of this study is to invistgate the characteristics of Si-MOSFET with 18 nm length of ion implemented channel. Technology computer aided design (TCAD) tool from Silvaco was used to simulate the MOSFET’s designed structure in this research. The results indicate that the MOSFET with 18 nm channel length has cut-off frequency of 548 GHz and transconductance of 967 μS, which are the most important factors in calculating the efficiency and improving the performance of the device. Also, it has threshold voltage of (-0.17 V) in addition obtaining a relatively small DIBL (55.11 mV/V). The subthreshold slope was in high value of 307.5 mV/dec. and this is one of the undesirable factors for the device results by short channel effect, but it does not reduce its performance and efficiency in general.